2022
DOI: 10.3354/esr01189
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year impact of white-nose syndrome on tri-colored bat (Perimyotis subflavus) populations in Georgia, USA

Abstract: White-nose syndrome (WNS) has emerged as the most serious threat to North American cave-dwelling bat species, with an estimated mortality of over 6 million since it was first documented in the USA in 2006. Tri-colored bat Perimyotis subflavus is one of the species most affected, with hibernaculum counts at caves in WNS-positive regions reduced by >90% from previous counts. While declines have been documented in hibernaculum surveys, long-term monitoring programs during active seasons provide a unique opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Population declines in tricolored bat hibernaculum counts in our study are consistent with patterns in other WNS-positive regions of the eastern United States (Langwig et al 2012, Powers et al 2015, Frick et al 2017, Loeb and Winters 2022. Trends are similar to those found during hibernation (Loeb and Winters 2022) and activity patterns during summer obtained from acoustic monitoring (Perea et al 2022) along the periphery of the white-nose syndrome endemic region. Our results indicated a decline of approximately 90% in the first 3 years after WNS detection, followed by stabilization, as has been documented in hibernating populations of tricolored bats in other regions (Frick et al 2017, Loeb andWinters 2022).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Population declines in tricolored bat hibernaculum counts in our study are consistent with patterns in other WNS-positive regions of the eastern United States (Langwig et al 2012, Powers et al 2015, Frick et al 2017, Loeb and Winters 2022. Trends are similar to those found during hibernation (Loeb and Winters 2022) and activity patterns during summer obtained from acoustic monitoring (Perea et al 2022) along the periphery of the white-nose syndrome endemic region. Our results indicated a decline of approximately 90% in the first 3 years after WNS detection, followed by stabilization, as has been documented in hibernating populations of tricolored bats in other regions (Frick et al 2017, Loeb andWinters 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Differences in population decline following the introduction of Pd have been documented over time periods ranging from 1 to 5 years, varying by species and region (Bernard and McCracken 2017, Frick et al 2017, Barr et al 2021). In a long‐term acoustic monitoring study in Georgia, Perea et al (2022) observed declines in relative activity of tricolored bats 2 years after WNS detection, with activity reaching a stable minimum 3 years after the disease was first documented in northern Georgia (USFWS 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bats in hibernacula infected with WNS have more activity than noninfected hibernacula, including flights over the landscape in cooler temperatures (Bernard and McCracken, 2017). In addition to observed fatalities at hibernacula, WNS has also been linked to decreased regional populations (Turner et al, 2011;Ingersoll et al, 2013;Ingersoll et al, 2016;Perry and Jordan, 2022), cave-bat abundance in summer habitats (Dzal et al, 2010;Brooks, 2011;O'Keefe et al, 2019, Deeley et al, 2021Johnson et al, 2021;Loeb and Winters, 2022;Perea et al, 2022) as well as winter hibernacula (Lacki et al, 2015;Powers et al, 2015;Perry and Jordan, 2020).…”
Section: Effects Of Temperature On Bat Migration and Flight Activitymentioning
confidence: 99%